Public Library services to the Polish community living in Iceland: A review of multicultural services offered by the Reykjavik City Library and the important role of the Polish Library in Reykjavik - Aneta Beata Wlodarczyk 1978- (2017)
Multiculturalism is a new phenomenon in Iceland. With the increase in cultural diversity comes a challenge to public institutions to provide minorities with access to political, economic, educational and public resources. Libraries are considered key institutions that can effectively support the idea of multiculturalism, promote equality, keep linguistic heritage and maintain culture. One of the ways in which libraries reach out to culturally diverse populations is through multicultural library services, which aim to address informational, educational, cultural and literary needs. The purpose of this paper is to review the multicultural services offered by Reykjavik Public Library as well as the importance of the Polish Library to the Polish community living in Iceland. Reykjavik Public Library’s aim is to promote awareness of positive multicultural values and cultural diversity in the society. The library offers plenty of interesting projects targeting immigrants from various countries; however the multicultural nature of Reykjavik is not reflected in the library collection, at least not in the case of the Polish community. The Polish Library in Reykjavik is striving to address the reading needs of the growing Polish community. Icelandic libraries as public institutions must evolve and be involved in multicultural issues in order to contribute towards social inclusion of immigrants. Furthermore, the fundamental human rights of equal access to library services have to be employed. Fjölmenning er nýtt fyrirbæri á Íslandi. Aukin fjölmenning hefur það í för með sér að opinberar stofnanir í landinu standa frammi fyrir þeirri áskorun að tryggja minnihlutahópum aðgengi að pólitískum, efnahagslegum, menntunarlegum og opinberum úrræðum. Fjölmenning leggur áherslu á grunnhluti með virðingu við menningarlegan mismun, ferlið við að varðveita menningarlega sjálfsmynd og að tryggja minnihlutahópum jafnrétti og aðgengi að pólitískum, efnahagslegum, menntunarlegum og opinberum úrræðum. Bókasöfn eru talin vera lykilstofnanir ...